CoCl2 as film morphology controller for efficient planar CsPbIBr2 perovskite solar cells. (20th July 2020) - Sun, Hongrui; Yu, Luting; Yuan, Haobo; Zhang, Jing; Gan, Xinlei; Hu, Ziyang; Zhu, Yuejin
Abstract: High quality perovskite (PVK) film is quite important to reduce the energy loss (Eloss) and enhance the performance of planar CsPbIBr2 PVK solar cells (PSCs). In this work, 5% PbBr2 is substituted by CoCl2 in inorganic CsPbIBr2 PVK, acting as film morphology controller to slow down the crystallization process. It results in a dense and flat pinhole-free CsI(PbBr2)0.95(CoCl2)0.05 PVK film. Therefore, the trap state density is greatly reduced, which lead to reduce non-radiative recombination of carriers and Eloss, therefore, the open-circuit voltage (Voc) of the device is increased from 1.14 V of control sample to 1.25 V. The optimal photoelectric conversion efficiency (PCE) is enhanced to 10.43% relative to 6.93% of CsPbIBr2 PSCs. More importantly, the air stability of CsI(PbBr2)0.95(CoCl2)0.05 PSCs is greatly enhanced, which still maintain above 90% in the air of 25 °C and RH = 20% for 25 days without encapsulation. This work highlights the great effect of CoCl2 as a morphology controller on improving CsPbIBr2 film quality and device performance.